1971
DOI: 10.1139/b71-232
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of isocitrate lyase from autotrophic and photoheterotrophic cultures of Gloeomonas sp.

Abstract: Isocitrate lyase (EC. 4.1.3.1) has been partially purified from extracts of the unicellular green alga Gloeomonas sp. grown either photoautotrophically in CO2 or photoheterotrophically with acetate resulting in a 50-fold increase in specific activity. Enzyme preparations from both cultures were eluted from DEAE-cellulose columns at almost the same position. The enzymes showed classical Michaelis kinetics with Km values of 1.14 and 1.4 mM and responded in a similar manner to metabolites. Glycol-late, 3-phosphog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
8
0
1

Year Published

1972
1972
1974
1974

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 13 publications
3
8
0
1
Order By: Relevance
“…The enzyme has shown an apparent Km of 0.1 mm at pH 7.4 in phosphate buffer. The enzyme is susceptible to end product inhibition by succinate (Table V) as well as inhibition by oxaloacetate, DL-malate, glycolate, and 3-phosphoglycerate at 10 mm in a manner similar to that reported for algal enzyme (7). It also showed an unusual activation by ribulose-1, 5-diP.…”
Section: Demonstration Of Isocitrate Lyase Activity In Darkenedsupporting
confidence: 67%
See 3 more Smart Citations
“…The enzyme has shown an apparent Km of 0.1 mm at pH 7.4 in phosphate buffer. The enzyme is susceptible to end product inhibition by succinate (Table V) as well as inhibition by oxaloacetate, DL-malate, glycolate, and 3-phosphoglycerate at 10 mm in a manner similar to that reported for algal enzyme (7). It also showed an unusual activation by ribulose-1, 5-diP.…”
Section: Demonstration Of Isocitrate Lyase Activity In Darkenedsupporting
confidence: 67%
“…Harrop and Kornberg (12) suggested that the presence of isocitrate lyase in autotrophic green algae would not necessarily implicate the operation of glyoxylate cycle to replenish the C4 acids as in algae or bacteria grown on acetate (14), since these acids could arise by the /8-carboxylation of phosphoenolpyruvate. This was supported further by the reports of Foo et al (7) and Badour and Waygood (2).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…1). (Foo et al 1971). I n der Zelle setzt ein gesteigerter ATP-Spiegel (neben der Substratphosphorylierung) eine aktive terminale Oxydation und damit gekoppelt einen hohen Reduktionsgrad der Gesamtheit der Cosubstrate NADund in entsprechendem AusmaB -NADP voraus.…”
Section: Ergebnisse Uizd Diskussionunclassified